Case report: genetic analysis of a child with 18q deletion syndrome and developmental dysplasia of the hip - Shufeng Yu; Caixia Wang; Ke Lei; Xuefei Leng; Lijuan Zhang; Fei Tian; Zhihong Chen (BMC, 2022)
Abstract Objective To analyze the genotypes and phenotypes of a child with developmental dysplasia of the hip (DDH), developmental delays, recurrent fever, hypothyroidism and cleft palate. Methods G-banding karyotyping analysis and next-generation sequencing (NGS) were performed for the patient. The genotypes of the parents of the patient were verified by copy number variation analysis and Sanger sequencing to determine the source of variations. Results The karyotype of the patient was 46, XX. A 10.44 Mb deletion (chr18:67562936-78005270del) at 18q22.2q23 was found by NGS. We identified 2 HSPG2 mutations (chr1: 22206699, c.2244C > A, exon 17, p.H748Q; chr1: 22157321-22157321, c.11671 + 154insA, intron). One mutation was inherited from the father, and the other was inherited from the mother. Conclusion This is the first 18q deletion syndrome case accompanied by DDH. Most phenotypes of this patient, such as developmental delays and cleft palate, may be related to the 18q22.2q23 deletion, but no variants in genes related to DDH were found in this deletion region. DDH may be related to mutations of HSPG2.